Pengaruh Kualitas Pelayanan Islami Terhadap Kepuasan Pelanggan Pada Salon Muslimah Sayyidah Depok - Rinjani, Adissa Nanda (Educationist: Journal of Educational and Cultural Studies, 2023)
This study aims to determine the effect of assurance, responsiveness, tangbles, empathy, and reliability on customer satisfaction at Salon Muslimah Sayyidah Depok. This research is a quantitative research, using a survey method, namely through the distribution of Google Forms to customers of Salon Muslimah Sayyidah. Sampling in this study was using a purposive sampling technique, and the sample in the study was 135 respondents. Data analysis used structural equation modeling techniques using SmartPLS 3.0 software. The results of this study indicate that the variables assurance, responsiveness, tangibles, empathy, and reliability have proven to have a positive and significant effect on customer satisfaction at Salon Muslimah Sayyidah. The assurance variable provided by Salon Muslimah Sayyidah is a factor that greatly influences customer satisfaction.